Effects of Centella asiatica L. Capsul on Muscle Disfunction on Elderly People - I Dewa Putu Pramantara; Nyoman Nyoman Kertia; Mae Sri Hartati Wahyuningsih; Nur Arfian (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Pegagan (Centella asiatica L) has been traditionally used to treat wounds, disordered nerve system, blood circulation, and prevent muscle disorders. Extract of Pegagan was considered safe and non-toxic as the acuut and chronic toxicity tests on male SD rats were not significant. It meant that further study was potential to be proceeded. Study of C.asiatica on muscle function of the elderly has not been done, therefore this study is aimed to observe effects of C.asiatica extract on muscle masses, holding hands, walking speed (4.57 meter), walking test (6 minutes), and Time Up and Go test of the elderly. This study is designed for clinical double blind study with 2 groups of people, these are C. asiatica (18 people) treated with capsul (550 mg C. asiatica extract/day for 90 days) and placebo (17 people). This study is performed in the RSUP Dr. Sardjito hospital at the geriatric division. Subjects for this study were healthy elderly people and fit with the criteria of subjects for experiment. Result of the study, muscle masses do not decrease and all the measurements are not different with that of placebo. Except that the walking speed (6 minutes) of the treated subjects is better than that of the placebo. The conclusion of the study, the capsul containing C. asiatica extract (550 mg, once a day for 90 days) increases the strengh of hands holding, and the walking test (6 minutes) almost twice better than that of the placebo although the muscle masses does not increase significantly.